Revealing the inner worlds of young children : the MacArthur story stem battery and parent-child narratives - Emde, Robert N.; Wolf, Dennie; Oppenheim, David, 1958- (Oxford University Press, 2003)
Typically, we make sense of our experiences and interactions in a way that is guided by emotion and that takes the form of a narrative or a story. Using narratives, we can tell others about our experience, share common meanings, imagine possibilities, and co-construct new meanings. It is thus a momentous development when, at around age three, a child acquires the capacity to construct narratives. The book reports the work of a 20-year collaboration between 36 psychologists who have created and investigated a new tool to elicit and analyze children's narratives. This tool is the MacArthur Story Stem Battery, a systematic collection of story beginnings that are referred to as 'stems.' These stems are designed to elicit information from children about their representational worlds. This method is particularly exciting because using it allows developmental psychologists to gain information directly from children about their emotional states and what they are able to understand, and in turn, to use this information to explore significant emotional differences among children.
Keywords: Storytelling ability in children.; Cognition in children.; Children -- Language.; Preschool children.; Cognition.; Emotions.; Narrative medicine.; Child psychology.; Verbal behavior.; Children.; Child Language; Child, Preschool; Cognition; Emotions; Interview, Psychological; Narration; Psychology, Child; Verbal Behavior; Child; Art de conter chez l'enfant.; Cognition chez l'enfant.; Enfants -- Langage.; Enfants d'âge préscolaire.; Émotions.; Médecine narrative.; Enfants -- Psychologie.; Comportement verbal.; Enfants.; Enfance.; cognition.; emotion.; children (people by age group); childhood.; PSYCHOLOGY -- Developmental -- Child.; PSYCHOLOGY -- Psychotherapy -- Child & Adolescent.; FAMILY & RELATIONSHIPS -- Child Development.; Verbal behavior; Preschool children; Narrative medicine; Children; Child psychology; Children -- Language; Cognition in children; Storytelling ability in children; Education.; Electronic books.